Curcumin as an effective suppressor of miRNA expression in patients with knee osteoarthritis - Mahdi Atabaki; Zhaleh Shariati-Sarabi; Jalil Tavakkol-Afshari; Ali Taghipour; Mahmood Reza Jafari; Amin Reza Nikpoor; Mojgan Mohammadi (Mashhad University of Medical Sciences, 2022)
Objective: Osteoarthritis is the most common disease in the group of joint diseases, and its incidence is directly related to aging. Given the anti-inflammatory effects of curcumin as an active ingredient of turmeric, we aimed to investigate the effects of this compound in a new curcumin nanomicelle formula named SinaCurcumin® on the expression of microRNAs (miRNAs) involved in immune responses of patients with osteoarthritis.Materials and Methods: We divided 30 patients with osteoarthritis into two groups namely, nano curcumin-receiving (15 patients) and placebo-receiving (15 patients) and we studied them for 3 months. The Iranian Registry of Clinical Trials (IRCT) approved our study with the IRCT registry No. IRCT20151028024760N4. We evaluated the rates of the expression of microRNAs 146, 155, 16, and 138 employing SYBR Green Real-Time PCR method.Results: The expression of miRNAs 155, 138, and 16 revealed a significant reduction in the curcumin-receiving group (p=0.002, p=0.024 and p=0.0001 respectively).Conclusion: Our research data indicated that the consumption of curcumin in patients with osteoarthritis could affect the immune system partially via altering the expression of microRNAs and cytokines.